(3GdQSGdI GdefaPI Edi GdbGVjs ((3MeRg Hf Ydi Hf CMeO s)
(3ChdgG (B:s
(3ef YHO CejQ GdeDefjf heedhcg MeRI Hf Ydj Hf CMeO gGOj GdeSJLjHjf s
(3BNQgG (B:s
(3GdoefJbe ef GdeTQcjf HSja ehdGfG CejQ GdeDefjf hgh MSHj hfYe GdfUjQ GdoeYjf s
(3Vef eLehY , JQJjHgG (B: 15s
(3QSGdI ef QSGFd GdOQhRs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdeQjcjI aj HjQhJ s
Keywords: (3GdJhMjO hGdedd hGdfMds